Developing and Evaluating Instructional Supervision Programs to Enhance Teacher Performance: A Case Study of SMK Negeri 1 Buntok, Indonesia - Dwi Septian; Khairunnisa Khairunnisa; Khairatunnisa Khairatunnisa; Sulistiyana Sulistiyana; Metroyadi Metroyadi (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: Instructional supervision is an essential component of the teacher professional development system aimed at improving the quality of learning processes and outcomes. This study aims to develop and evaluate an effective instructional supervision program to enhance teacher performance at SMKN 1 Buntok. A descriptive qualitative approach was employed, focusing on the implementation process of supervision, program development, and the evaluation of its impact on teacher performance improvement. Data were collected through in-depth interviews, observations, and document studies involving the principal, school supervisors, and teachers. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The results show that instructional supervision at SMKN 1 Buntok was previously administrative in nature and had not yet focused on professional teacher development. Through the development of a supervision program designed based on teacher needs, its implementation became more structured, collaborative, and reflective. Evaluation of the supervision program indicated significant improvements in teacher performance, particularly in lesson planning, teaching implementation, and teachers’ ability to reflect on student learning outcomes. The theoretical framework used in this study includes concepts of instructional supervision, supervision program development, supervision evaluation, and teacher performance, which collectively demonstrate that well-planned supervision development and evaluation can foster continuous improvement in teacher professionalism and performance. Keywords: Instructional supervision; teacher performance; professional development; qualitative study; supervision program evaluation; SMKN 1 Buntok